CIPLUKAN (PHYSALIS ANGULATA LINN.) EXTRACT AS A NATURAL ADJUVANT REMEDIES FOR SCLERODERMA - Lintang Unggul Rini (Berkala Ilmiah Kedokteran Duta Wacana, 2020)
Scleroderma or systemic sclerosis is a rare connective tissue autoimmune disorder.1 Its prevalence in Indonesia is not well recorded but scleroderma is listed as the third most common disease in rheumatology outpatient clinic in Hasan Sadikin Hospital, Bandung, West Java, Indonesia.2,3 Scleroderma is characterized by skin fibrosis, small vessel vasculopathy, and immune system abnormality. The cutaneous lesion of scleroderma is presenting with excessive collagen type-1 production and deposition, as well as exaggerated inflammatory process. There is no specific diagnosis test is available, but in most cases, there are some laboratory findings which support the diagnosis of scleroderma, such as elevated erythrocyte sedimentation rate (ESR), B lymphocyte stimulator (BAFF), C-Reactive Protein (CRP), Soluble Cd40 Ligand (sCD40L), and Procollagen Type-1 N-Terminal Propeptide (P1NP).3-6 The treatment of this autoimmune disease remains a challenge for clinicians. The current treatment for scleroderma is expensive and some side effects as well as drug resistance are reported. Some new medicines are still under research, not accessible, and too expensive for most Indonesian communities. Hence, new therapeutic options are constantly sought.7 Ciplukan herb (Physalis angulate Linn) is a medicinal plant which grows in Indonesia. It has been known for its efficacy and safety as long-term anti-inflammatory, anti-proliferative, and anti-angiogenesis agent.7 Dewi et al conducted a double –blind, randomized clinical trial using ciplukan herb extract as an adjuvant treatment for scleroderma. The clinical trial was performed in Jakarta and Bandung, Indonesia for 2 years. There are 59 scleroderma patients, age 15-60 years old, had stable treatment for at least 3 months, who randomly divided into treatment group (29 people) and control group (30 people). The treatment group received 250 mg ciplukan herb extract three times a day and the control group received 250 mg amylum three times a day for 12 weeks. A 35,9% skin thickness reduction was found in treatment group. It is greater than control group which only gained 6,3% reduction (p